Adsorption of fluorinated greenhouse gases on activated carbons: evaluation of their potential for gas separation - Sosa, Julio E. (2022)
Funding of the KET4F-Gas project, SOE2/P1/P0823, co-funded by the Interreg Sudoe Program through the European Regional Development Fund (ERDF). A.B. Pereiro and J.M.M. Araújo acknowledge FCT/MCTES for financial support through IF/00190/2014 contract and IF/00210/2014 contract, respectively. Rui Ribeiro acknowledges financial support through the Norma Transitória DL 57/2016 Program Contract (FCT/MCTES). This work was also supported by the Associate Laboratory for Green Chemistry ? LAQV, which is financed by national funds from FCT/MCTES (UID/QUI/50006/2019).